From the Editor's Desk - Russel K Hirst (International Journal of Nuclear Security, 2019)
We are happy to present to you IJNS issue 5.1, 2019. This issue contains a welcome variety of articles speaking to many practical matters in nuclear security and safety, and in education and international policy. All these themes are invaluable as we continue our worldwide conversations among scholars and professionals, as well as with global citizens concerned for keeping our world safe from nuclear accident and aggression. We are pleased to include five articles and four book reviews in this issue.